Development of an Agrobacterium tumefaciens-mediated transformation system for somatic embryos and transcriptome analysis of LcMYB1’s inhibitory effect on somatic embryogenesis in Litchi chinensis - Yaqi Qin; Bo Zhang; Xueliang Luo; Shiqian Wang; Jiaxin Fu; Zhike Zhang; Yonghua Qin; Jietang Zhao; Guibing Hu (Journal of Integrative Agriculture)
Litchi has great economic significance as a global fruit crop. However, the advancement of litchi functional genomics has encountered substantial obstacles due to its recalcitrance to stable transformation. Here, we present an efficacious Agrobacterium tumefaciens-mediated transformation system in somatic embryos of ‘Heiye’ litchi. This system was developed through the optimization of key variables encompassing explant selection, A. tumefaciens strain delineation, bacterium concentration, infection duration, and infection methodology. The subsequent validation of the transformation technique in litchi was realized through the ectopic expression of LcMYB1, resulting in the generation of transgenic calli. However, the differentiation of transgenic calli into somatic embryos encountered substantial challenges. To delineate the intricate molecular underpinnings of LcMYB1’s inhibitory role in somatic embryo induction, a comprehensive transcriptome analysis was conducted that encompassed embryogenic calli (C), globular embryos (G), and transgenic calli (TC). A total of 1,166 common differentially expressed genes (DEGs) were identified between C-vs.-G and C-vs.-TC. Gene Ontology (GO) annotation and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis revealed that these common DEGs were mostly related to plant hormone signal transduction pathways. Furthermore, RT-qPCR corroborated the pronounced down-regulation of numerous genes that are associated with somatic embryo induction within the transgenic calli. The development of this transformation system provides valuable support for functional genomics research in litchi.